(untitled) (مجلة إحالات, 2026)
The Pandemic disrupted the teaching-learning process in universities around the world, forcing academic bodies to adopt new teaching models, such as virtual and distance learning. As a Spanish language teacher, I found myself facing challenges, with new teaching methods to achieve the teaching-learning process. In this article, I will discuss my own experience in teaching literature at a distance.